Three-dimensional printed model and transantral endoscopy to orbital fracture repair - Moura, Lucas Borin [UNESP]; de Azambuja Carvalho, Pedro Henrique [UNESP]; Gabrielli, Marisa Aparecida Cabrini [UNESP]; Pereira-Filho, Valfrido Antonio [UNESP] (Wolters Kluwer, 2018)
Orbital fractures are high prevalent and result in several complications such as diplopia, muscular entrapment, visual impairment, and enophthalmos. The goal of orbital reconstruction is to restore orbital anatomy, volume, and globe symmetry. This case report aims to describe the use of transantral endoscopy and 3D printed model for treatment of an orbital floor fracture. A 54-year-old woman presented orbital floor fracture with diplopia and extraocular muscle entrapment. The surgical treatment was performed using a standard titanium mesh bended over 3D printed model, and transantral endoscopy to verify fracture extension and implant adaptation. The postoperative evaluation demonstrates correction of diplopia and ocular motility restriction. Computed tomography scan showed reestablishment of the orbital anatomy. The association of transantral endoscopy and 3D printed models is a feasible technique to improve orbital reconstruction.
Keywords: Blowout fracture; Endoscopic repair; Orbital floor; Three dimensional printing